PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. MATAHARI PUTRA PRIMA Tbk. (HYPERMART SUN PLAZA) MEDAN - Sinaga, Ria Veronica (UNIKA Santo Thomas, 2017)
This study aims to determine the effect of service quality which consists of (tangibles, reliability, responsiveness, assurance, and empathy) to customer satisfaction of PT. Matahari Putra Prima (Hypermart Sun Plaza) Medan. The benefits of research is to provide input for the company in order to formulate marketing strategies and to contribute to researchers in the field of marketing science. The sample size is 96 respondents. Data collection techniques used were questionnaires and documentation. Data analysis method used is multiple regression analysis. Based on the result of research, the regression equation is obtained as follows: Y = 3,359 + 0,131x1 + 0,174x2 + 0,196x3 + 0,236x4 + 0,374x5. Based on the analysis of statistical data, the indicators in this study are valid and the variables are reliable. In the classical assumption test, the regression model is normally distributed, free of multicolonearity, and no heteroscedasticity occurs. The individual sequence of each of the most influential variables is the emphaty variable with the regression coefficient of 0.374; Then assurance with regression coefficient 0.236; Then followed by responsiveness with regression coefficient 0,196 and reliability with regression coefficient 0,174; While the variable that has the lowest effect is tangible with regression coefficient 0,131. PT. Matahari Putra Prima (Hypermart Sun Plaza) Medan in improving customer satisfaction is expected to not only use and execute strategy of applying service quality only but must cover all components related to marketing and have relationship with customer satisfaction. Problems or other aspects that may affect customer satisfaction can be a quality product, price, promotion, and place.